Analysis of Composition, Structure, and Driving Factors of Root-Associated Endophytic Bacterial Communities of the Chinese Medicinal Herb Glycyrrhiza - Zhilin Zhang; Aifang Ma; Tao Zhang; Li Zhuang; Hanli Dang (Biology, 2025)
The role of endophytic bacteria in the interaction between medicinal plants and microorganisms, secondary metabolite accumulation, plant nutrient changes, as well as their interactions with microbial communities, needs to be investigated in medicinal plants. In this study, 16S rRNA genes of endophytic bacterial communities in the root systems of three medicinal licorice species at different root depths (0–20, 20–40, and 40–60 cm) were sequenced using high-throughput sequencing technology, and their relationships with plant and soil factors were investigated. Our study indicated that the influence of Glycyrrhiza species on the structure of endophytic bacterial communities is significantly greater than that of root depth, and there are significant differences in the structure of endophytic bacterial communities at different sampling sites. At the phylum level, Proteobacteria and Actinobacteria are the dominant phylum. Functional gene prediction shows that functional genes related to metabolism dominate the endogenous bacterial community. Plant factors and soil physicochemical properties are important environmental drivers affecting the distribution of endophytic bacterial communities. This study will give new information on plant–soil–endophyte interactions and open up new possibilities for medicinal licorice development and use.